Evaluation of Quality of Life (QoL) of Patients with Adolescent Idiopathic Scoliosis (AIS) after Surgical Correction - Mohamed A Abdelaziz, MD. (Egyptian Spine Association, 2020)
Background Data: Adolescent Idiopathic Scoliosis (AIS) is a spinal deformity that may interfere with patients’ quality of life. Many previous studies tried to assess the health-related quality of life (HRQoL) using the patient-reported outcome measures. The Arabic version of Scoliosis Research Society 22 (SRS-22r) questionnaire is known to be reliable and a valid tool to assess the quality of life in patients with AIS. Purpose: To evaluate quality of life of patients with AIS after surgical correction using the Arabic version of Scoliosis Research Society 22 (SRS-22r) questionnaire. Study Design: Prospective cohort study. Patients and Methods: Between 2016 and 2018, twenty-five patients were surgically treated for AIS with Cobb’s angle >45 degrees. All patients underwent posterior derotation and instrumented correction and fusion technique. In this study, we used the Arabic version of SRS-22 questionnaire to evaluate the clinical patient’s outcome. Whole spine plain X-ray was utilized to assess the radiological outcome. All patients underwent postoperative follow-up for at least 6 months with the SRS-22r questionnaire conducted in the last visit. Results: Twenty-five patients were recruited for this study including 22 females and 3 males with mean age of 14.7±1.7 (range, 11–18) years. Significant improvement was reported 6 months after surgical correction in the following radiological parameters: Cobb’s angle of the primary curve from 55.81±8.72 to 7.98±2.26; pelvic incidence from 62.24±7.33 to 57.96±6.14; pelvic tilt from 26.14±3.41 to 20.76±3.74; lumbar lordosis from 33.21±8.63 to 36.6±8.79. The scores of functional activity, pain, self-image/appearance, mental health, and satisfaction were 4.31±0.28, 4.57±0.27, 4.85±0.31, 4.85±0.17, and 4.96±0.21, respectively, at the last follow-up visit. The total SRS-22 score was 4.45±0.16. Correlation between different domains of SRS-22 questionnaire after surgical correction shows that only function/activity score revealed a positive significant correlation with the mental health domain (r=0.417) (P=0.038). Conclusion: The Arabic version of SRS-22 questionnaire was very useful in terms of measuring patients’ perceptions. Self-image domain was showing the highest increase among all other domains. (2019ESJ195)